The ESSO core curriculum committee update on surgical oncology. Issue 11 (November 2021) - van der Hage, Jos; Sandrucci, Sergio; Audisio, Riccardo; Wyld, Lynda; Søreide, Kjetil; Amaral, Teresa; Audisio, Riccardo; Bahadoer, Viren; Beets, Geerard; Benstead, Kim; Berge Nilsen, Elisabeth; Bol, Kalijn; et al.
Abstract: Introduction: Surgical oncology is a defined specialty within the European Board of Surgery within the European Union of Medical Specialists (UEMS). Variation in training and specialization still occurs across Europe. There is a need to align the core knowledge needed to fulfil the criteria across subspecialities in surgical oncology. Material and methods: The core curriculum, established in 2013, was developed with contributions from expert advisors from within the European Society of Surgical Oncology (ESSO), European Society for Radiotherapy and Oncology (ESTRO) and European Society of Medical Oncology (ESMO) and related subspeciality experts. Results: The current version reiterates and updates the core curriculum structure needed for current and future candidates who plans to train for and eventually sit the European fellowship exam for the European Board of Surgery in Surgical Oncology. The content included is not intended to be exhaustive but, rather to give the candidate an idea of expectations and areas for in depth study, in addition to the practical requirements. The five elements included are: Basic principles of oncology; Disease site specific oncology; Generic clinical skills; Training recommendations, and, lastly; Eligibility for the EBSQ exam in Surgical Oncology. Conclusions: As evidence-based care for cancer patients evolves through research into basic science, translational research and clinical trials, the core curriculum will evolve, mature and adapt to deliver continual improvements in cancer outcomes for patients.